Must losing taxes on saving be harmful? - Harry Huizinga; Søren Bo Nielsen (Copenhagen Business School (CBS), Department of Economics, 2004)
Internationalization offers enhanced opportunities for individuals to place savings abroad and evade domestic saving taxation. This paper asks whether the concomi- tant loss of saving taxation necessarily is harmful. To this end we construct a model of many symmetric countries in which public goods are financed by taxes on saving and investment. There is international cross-ownership of firms, and countries are assumed to be unable to tax away pure profits. Countries then face an incentive to impose a rather high investment tax also borne by foreigners. In this setting, the loss of the saving tax instrument on account of international tax evasion may prevent the overall saving-investment tax wedge from becoming too high, and hence may be beneficial for moderate preferences for public goods. A world with 'high-spending' governments, in contrast, is made worse off by the loss of saving taxes,and hence stands to gain from international cooperation to restore saving taxation.
hdl:10398/7535
Keywords: H21; H87; 330; Capital income taxation; cross-ownership; coordination